IMPACT OF CHILD LABOUR THROUGH SUGARCANE GROWING ON ACADEMIC PERFORMANCE IN SELECTED PRIMARY SCHOOLS IN WAIBUGA SUB COUNTY, LUUKA DISTRICT: A CROSS-SECTIONAL STUDY. - Mbago , Livingstone; Nzanzu , Joshua Twalibu; Arinitwe, Winfred; Mugenyi, Harriet (Student’s Journal of Health Research Africa, 2024)
Background The study sought to investigate the impact of child labor through sugarcane growing on the academic performance in primary schools of Waibuga Sub County in Luuka District. Methodology. A cross-sectional study design was used and a review of primary documents, review of secondary documents, interview method, focus group discussion, and observation method were used. Asked the extent to which children are involved in sugarcane growing. Results. 5 out of 100 respondents representing 5% said to a very big extent, 45 out of 100 respondents representing 45% said to a big extent, while 50 respondents representing 50% said to a small extent. 40 out of 100 respondents representing 40% said to a very big extent, 50 out of 100 respondents representing 50% said to a big extent, while only 10 respondents out of 100 representing 10% said to a small extent. Conclusion There is a significant correlation between child labor and academic performance. Recommendation. There is a dire need for the Government of Uganda to enact laws.